PENERAPAN GAMIFIKASI SEBAGAI UPAYA PENINGKATAN MOTIVASI BELAJAR SISWA AKUNTANSI PADA SALAH SATU SMK DI KARANGANYAR TAHUN AJARAN 2024/2025 - Amelia Eka Nuraini; Muhtar Muhtar; Sri Sumaryati (Universitas Sebelas Maret, 2025)
AbstractThis study aimed to describe the improvement of students’ learning motivation. It was a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 17 students of Class XI Accounting and Financial Institution (AKL) at SMK in Karanganyar. The data collection techniques used were observation, questionnaires, and documentation. The validity of the instruments was tested using source triangulation, method triangulation, and construct validity. The data analysis techniques used were quantitative data analysis. The results of the study showed that the implementation of the gamification learning model improved students’ learning motivation. In the pre-action stage, 7 students (42%) had low learning motivation. In the first cycle, 12 students (70%) showed high learning motivation. In the second cycle, the number of students with high learning motivation increased to 14 students (83%). Therefore, it was concluded that the implementation of the gamification learning model improved students’ learning motivation.Keywords: Classroom Action Research, Gamification Learning Model, Students' Learning Motivation. AbstrakPenelitian ini memiliki tujuan untuk mendeskripsikan peningkatan motivasi belajar siswa. Studi ini termasuk Penelitian Tindakan Kelas (PTK) yang dilakukan melalui dua siklus, dengan tiap siklus mencakup tahap perencanaan, pelaksanaan, observasi, serta refleksi. Subjek penelitian ini ialah siswa kelas XI Akuntansi dan Keuangan Lembaga (AKL) salah satu SMK di Karanganyar dengan total 17 siswa. Teknik pengumpulan data yang dipergunakan yakni observasi, kuesioner, dan dokumentasi. Uji validitas instrumen yang dipergunakan triangulasi sumber, triangulasi metode, serta validitas konstruk. Teknik analisis data mempergunakan kuantitatif. Temuan studi memperlihatkan bahwasanya penerapan model pembelajaran gamifikasi mampu meningkatkan motivasi belajar siswa. Dalam tahap pra tindakan proporsi siswa yang mempunyai motivasi belajar rendah sebanyak 7 siswa (42%). Pada tahap siklus I proporsi siswa yang mempunyai motivasi belajar tinggi sejumlah 12 siswa (70%). Pada tahap siklus II proporsi siswa yang mempunyai motivasi belajar tinggi meningkat menjadi 12 siswa (83%). Untuk itu bisa diambil simpulan bahwasanya penerapan model pembelajaran gamifikasi bisa meningkatkan motivasi belajar siswa.Kata kunci: Penelitian Tindakan Kelas, Model Pembelajaran Gamifikasi, Motivasi Belajar Siswa